2017
DOI: 10.1186/s12864-017-3915-z
|View full text |Cite
|
Sign up to set email alerts
|

Histological and transcriptomic effects of 17α-methyltestosterone on zebrafish gonad development

Abstract: BackgroundSex hormones play important roles in teleost ovarian and testicular development. In zebrafish, ovarian differentiation appears to be dictated by an oocyte-derived signal via Cyp19a1a aromatase-mediated estrogen production. Androgens and aromatase inhibitors can induce female-to-male sex reversal, however, the mechanisms underlying gonadal masculinisation are poorly understood. We used histological analyses together with RNA sequencing to characterise zebrafish gonadal transcriptomes and investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 153 publications
7
27
0
Order By: Relevance
“…In human ovaries, IL1 mediates inflammatory processes during ovulation, fertilization and oocyte implantation (Polan et al, 1991;Garcia-Velasco and Arici, 1999) and is highly expressed in ovarian cancers (Aggarwal and Gehlot, 2009). In this work, we report a higher expression of IL1 in testes when compared to ovaries in adult zebrafish according to that previously found by Lee et al (2017), thus indicating that IL1 is expressed in a sex-dependent manner in fish. In sea bream gonads, IL1 was found in the cytoplasm of spermatogonia, spermatocytes and oogonia and its expression was higher during reproductive cycles suggesting a role in promoting proliferation in gametogenesis and spermatocyte differentiation (Chaves-Pozo et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…In human ovaries, IL1 mediates inflammatory processes during ovulation, fertilization and oocyte implantation (Polan et al, 1991;Garcia-Velasco and Arici, 1999) and is highly expressed in ovarian cancers (Aggarwal and Gehlot, 2009). In this work, we report a higher expression of IL1 in testes when compared to ovaries in adult zebrafish according to that previously found by Lee et al (2017), thus indicating that IL1 is expressed in a sex-dependent manner in fish. In sea bream gonads, IL1 was found in the cytoplasm of spermatogonia, spermatocytes and oogonia and its expression was higher during reproductive cycles suggesting a role in promoting proliferation in gametogenesis and spermatocyte differentiation (Chaves-Pozo et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…The two cytokines, IL1β and TNFα modulated the in vitro testosterone production in goldfish testis indicating their role in regulating sex steroids (Lister and van der Kraak, 2002). In the present work, we report a higher expression of IL1β in testes when compared to ovaries in adult zebrafish according to what previously found by Lee et al (2017), thus indicating that IL1β is expressed in a sex-dependent manner in fish. We did not find significant difference in Casp9 expression between testes and ovaries although higher expression in testes was also observed.…”
Section: Discussionsupporting
confidence: 91%
“…As known, zebrafish is considered as a class of undifferentiated gonochoristic species (Hoar and Randall, 1969). In recent years, evidences have been found that some synthetic chemicals in environment could affect the sexual differentiation of zebrafish (Chen et al, 2016;Hua et al, 2016;Lee et al, 2017;Santos et al, 2017;Delomas and Dabrowski, 2018;Shi et al, 2018;Yang et al, 2018), playing roles as environmental endocrine disruptors. Delomas and Dabrowski (2018) reported that down-regulation of E2 in juvenile zebrafish induced a male-biased development.…”
Section: Discussionmentioning
confidence: 99%